PEMBELAJARAN BERBASIS LINGKUNGAN UNTUK PENINGKATAN HOTS SISWA KELAS V MI COKROAMINOTO BANDINGAN SIGALUH BANJARNEGARA TAHUN PELAJARAN 2024/2025 - Ratih Ida Tristanti; Noor Aziz; Ahmad Khoiri (PT. Intelek Cendikiawan Nusantara, 2025)
The background to this research begins with initial observations which show that many students face challenges in understanding and answering questions related to HOTS. This research aims to improve HOTS skills in class V students at MI Cokroaminoto Bandingan Sigaluh Banjarnegara for the 2024/2025 academic year. The method adopted in this research is Classroom Action Research (PTK). The research process was carried out in two cycles with the steps of planning, implementing, observing and reflecting. The learning approach used is Environment-Based Learining, which aims to offer relevant, active and meaningful learning experiences by utilizing the surrounding environment as a learning resource. Data was collected through observation, documentation and evaluation of student learning outcomes. The results showed a substansial increase in students’ HOTS abilities. In the pre-cycle, only 3 students (20%) met the KKM standards. In cycle I, the number increased to 6 students (40%), and in cycle II, the total reached 13 students (86,67%). This increase shows that the Environment-Based Learning model is effetive in improving students’ understanding of HOTS=based questions. Increasing students participation and increasing concentration and interest in learning. Therefore, it can be concluded that implementing Environment-Based Learning is an effectife way to improve the HOTS abilities of class V students at MI Cokroaminoto Bandingan Sigaluh Banjarnegara. This model is recommended as an innovative and contextual learning alternative in an effort to increase HOTS in elementart schools students.